Transforming Islamic Boarding School Funding: Fundraising Management Strategies for the Sustainability of the Al-Hilal Orphan Tahfidz Islamic Boarding School - Redi Saldijah; Rian Hidayatullah; Muhamad Hilmi rasyad; Badrudin (al-Afkar, Journal For Islamic Studies, 2026)
Islamic boarding schools in Indonesia play an important role in the education and development of the younger generation, especially for orphans and the poor. However, the sustainability of pesantren operations often faces challenges, especially in the aspect of funding. This study aims to identify effective strategies, challenges, and innovations in fund management to support pesantren operations. A qualitative research method with a descriptive-analytical approach was used, involving in-depth interviews, observation, and document analysis. The results showed that the use of digital platforms, transparency in fund management, and diversification of funding sources were able to increase the effectiveness of fundraising. Innovations such as periodic donation programmes and strategic partnerships with the private sector are recommendations for the long-term sustainability of pesantren.